Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.24036/108234-019883
|View full text |Cite
|
Sign up to set email alerts
|

Diksi Dalam Teks Berita Siswa Kelas Viii SMP Negeri 6 Pariaman

Abstract: The purpose of this study were. (1)to describe the accuracy of diction in the news text of class VIII students of  SMP Negeri 6 Pariaman. (2)to describe the precision of diction in the news text of class VIII students of  SMP Negeri 6 Pariaman. This type of research is qualitative research with descriptive methods. This research was conducted at Pariaman State Middle School 6. The data of this study are qualitative data in the form of news text diction. The source of this research data is text news writing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Code mixing in data (21 is in the phrase of course which is an English phrase. Mixed code in data (22) is found in the phrase mixed feelings.…”
Section: Phrase Code Mixingmentioning
confidence: 95%
See 1 more Smart Citation
“…Code mixing in data (21 is in the phrase of course which is an English phrase. Mixed code in data (22) is found in the phrase mixed feelings.…”
Section: Phrase Code Mixingmentioning
confidence: 95%
“…According to [21] news text is a text that contains information about what happened and is still being discussed by many people. News text is text that contains information about actual and reliable events [22]. News text is a text that contains factual information about issues or events that are currently being discussed [19].…”
Section: Relevance In News Text Learningmentioning
confidence: 99%
“…Furthermore, the research by Pendari et al (2019) [12] examined news text of junior high school students grade VIII from SMP Negeri 6 Pariaman. They found that the use of diction has accuracy and precision in choosing the word.…”
Section: Introductionmentioning
confidence: 99%
“…Teks berita diajarkan di kelas VIII dengan bahasan unsur-unsur, struktur, dan kebahasaan. Struktur-struktur tersebut tersusun secara runtut yang akhirnya membentuk sebuah teks yang utuh (Pendari dan Amril, 2019). Salah satu surat kabar yang menggunakan eufemisme dalam menyampaikan berita adalah surat kabar Tempo.…”
unclassified